2012
DOI: 10.4187/respcare.01380
|View full text |Cite
|
Sign up to set email alerts
|

Potential Inadequacy of Automatic Tube Compensation to Decrease Inspiratory Work Load After at Least 48 Hours of Endotracheal Tube Use in the Clinical Setting

Abstract: BACKGROUND: Endotracheal tubes (ETTs) impose a substantial respiratory work load on mechanically ventilated patients. Automatic tube compensation (ATC) should overcome this flowdependent resistive work load; however, ETT resistance can be increased by tracheal secretions or ETT deformities. Our bench study investigated whether ATC provides effective respiratory work load relief in used ETTs. METHODS: We enrolled 20 critically ill patients requiring mechanical ventilation for longer than 48 hours. After extubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…[50][51][52] Oto et al 53 found that reduction in ETT resistance precludes the automatic tube compensation ventilator feature from completely overcoming ETT resistance. It also reinforces the fact that humidification devices should be chosen based on suspected duration of use, patient condition, and presence of thick secretions.…”
Section: Heated Humidification Versus Heat-and-moisture Exchangers Fomentioning
confidence: 99%
“…[50][51][52] Oto et al 53 found that reduction in ETT resistance precludes the automatic tube compensation ventilator feature from completely overcoming ETT resistance. It also reinforces the fact that humidification devices should be chosen based on suspected duration of use, patient condition, and presence of thick secretions.…”
Section: Heated Humidification Versus Heat-and-moisture Exchangers Fomentioning
confidence: 99%
“…15 L/min through 3.5 ETT has higher resistance than 15 L/min through 6.0 ETT), but children with 3.5 ETT generally breathe at lower flow rates than those who have 6.0 ETT [9]. Several studies demonstrate that PS or Automatic endotracheal Tube Compensation (ATC) overcome imposed resistance from the ETT or ventilator circuits [3,5,[10][11][12][13]. However, these studies do not factor in the resistance of the natural airway, and have not routinely measured the difference between effort of breathing before and after extubation.…”
Section: Introductionmentioning
confidence: 99%
“…5,18,31,49,51 Luminal narrowing due to secretion buildup correlates with increased airflow resistance that leads to increased work of breathing for the patient. 32,51 Physicians commonly evaluate suitability for extubation by conducting spontaneous breathing trials where the patient must breathe through the ETT. Reduction in ETT internal diameter caused by secretion accumulation results in significant increases in diaphragmatic effort, decreases in tidal volume and disruption in breathing patterns during weaning procedures.…”
Section: Introductionmentioning
confidence: 99%